In vitro and in vivo anti-diabetic and anti-hyperlipidemic effects of protein hydrolysates from Octopus vulgaris in alloxanic rats. (April 2018) - Ben Slama-Ben Salem, Rabeb; Ktari, Naourez; Bkhairia, Intidhar; Nasri, Rim; Mora, Leticia; Kallel, Rim; Hamdi, Safa; Jamoussi, Kamel; Boudaouara, Tahia; El-Feki, Abdelfettah; Toldrá, Fidel; Nasri, Moncef
Abstract: This study aims to examine the effects of non-hydrolyzed octopus ( Octopus vulgaris ) muscle proteins (NHOPs) and their hydrolysates (OPHs) on alloxan induced diabetes in Wistar rats (AIDR). Animals were allocated into seven groups of six rats each: control group (C), diabetic group (D) and diabetic rats treated with acarbose (D + Acar), non-hydrolyzed octopus proteins (D + NHOPs) and octopus proteins hydrolysates (D + OPHs) groups. The diabetic rats presented a significant increase in glycemic status such as α-amylase activity (in plasma, pancreas and intestine), hepatic glycogen, blood glucose and glycated hemoglobin (HbA1c) levels, as well as a significant decrease in the levels of plasma insulin and total hemoglobin compared to control group. In addition, plasma and liver contents in total cholesterol, triglycerides and LDL-cholesterol significantly increased in AIDR compared to control group. However, the daily administration of OPHs for 30 days improved the glucose tolerance test, the glycemic status of diabetic rats and corrected the lipid profiles. Further, a significant increase in the activities of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase and gamma-glutamyl transpeptidase as well as in the level of plasma bilirubin on diabetic status was observed, indicating considerable hepatocellular injury. OPHs treatment was found to attenuate the increased activities of the plasma enzymes produced by diabetes and caused a subsequent recovery towards normalization compared to the control group. By contrast, the NHOPs treatment was found to increase the glucose metabolic disorders in AIDR. These beneficial effects of OPHs were confirmed by histological findings in the hepatic and pancreatic tissues of diabetic treated rats. Indeed, they avoid lipid accumulation in the hepatocytes and protect the pancreatic β-cells from degeneration. Our results thus suggest that OPHs may be helpful in the preventing from diabetic complications by reversing hepatotoxicity. Graphical abstract: Unlabelled Image Highlights: Octopus protein hydrolysates (OPHs) were prepared by different proteolytic enzymes. OPHs were found to attenuate hyperglycemia in alloxan induced diabetic rats (AIDR). Orally administered OPHs were found to regulate lipid profile and pancreatic lipase in AIDR. Non-hydrolyzed proteins did not attenuate hyperglycemia and hyperlipidemia. OPHs could be used as ingredients to formulate functional foods.